Clinical Case Applications of Mitek® Tissue Anchors in Veterinary Orthopaedics - Edwards, M. R.; Taylor, R. A.; Franceschi, Ruth A. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The Mitek®a tissue anchor is a new device designed for reattaching avulsed tendons, ligaments and joint capsule to bone. This device has proven useful in human orthopaedics. Initially approved for use in Bankart repair (reattachment of glenohumeral ligament to anterior glenoid rim) procedures (1-3), the Mitek® anchor is now utilized in ligamentous repairs and tenodesis of the foot, ankle (4, 5) and wrist (6, 7). These devices have the advantages of biocompatibility, small size, impressive pullout strength, versatility and ease of application (8). In this study Mitek® anchors were used to repair avulsed or ruptured tarsal and phalangeal collateral ligaments, coxofemoral luxations and to provide stability to cruciate deficient stifles.This paper describes the use of Metek® tissue anchors to repair tendinous, ligamentous, and joint capsule ruptures and avulsions.
Keywords: Mitek® tissue anchor; Bankart repair; scapholunate tenodesis; osteosutures